Autism spectrum disorder and schizophrenia: boundaries and uncertainties. (September 2016) - Pina-Camacho, Laura; Parellada, Mara; Kyriakopoulos, Marinos
Summary: Autism and schizophrenia were placed in different diagnostic categories in DSM-III, having previously been considered as related diagnostic entities. New evidence suggests that these disorders show clinical and cognitive deficit overlaps and shared neurobiological characteristics. Furthermore, children presenting with both autism spectrum disorder (ASD) and psychotic experiences may represent a subgroup of ASD more closely linked to psychosis. The study of ASD and childhood schizophrenia, and their clinical boundaries and overlapping pathophysiological characteristics, may clarify their relationship and lead to more effective interventions. This article discusses the relationship through a critical review of current and historical dilemmas surrounding the phenomenology and pathophysiology of these disorders. It provides a framework for working with children and young people with mixed clinical presentations, illustrated by three brief fictional case vignettes.